Introduction to Speech : How to Gain Attention and Win Favour of the Audience? Perception Analysis - Vlašić, Jelena; Pletikos, Elenmari (2006)
This paper deals with speech introductions. We examined what are the specific purposes of introductions and which elements of introductions are used to achieve this goal. The main purposes of introductions are to gain the listener's attention, to provoke interest for the topic and to secure respect for the speaker. In this paper we compare what rhetorical textbooks, from Hellenistic to contemporary ones, advise about delivering the introduction of a speech, and we research how young people evaluate different types of speech introduction. A perception experiment is carried out on young people (n=43) and it shows how this particular audience estimate different elements of introduction. On the scale from 1 to 7 they evaluated introductory sentences of 33 selected speeches in categories: motivation for listening (I will listen to the following speech), interesting, witty, persuasive (reliable), modest and poetic. Statistical analysis establishes that there is a very high correlation coefficient (0, 86) between entire motivation and interesting topic, and a high correlation coefficient (0, 64) between motivated and persuasive. There is a weak correlation between motivated and poetic (0, 40) and motivated and witty (0, 29). Modesty has no contribution to the decision to listen to the speech, but it has also no negative influence (correlation coefficient between categories I will listen to and it is modest is 0, 19).
ENG